Positive experiences of a vocational rehabilitation intervention for individuals on long-term sick leave, the Dirigo project: a qualitative study - Åsa Andersén; Christian Ståhl; Ingrid Anderzén; Per Kristiansson; Kjerstin Larsson (BMC, 2017)
Abstract Background The process of returning to work after long-term sick leave can sometimes be complex. Many factors, (e.g. cooperation between different authorities and the individual as well as individual factors such as health, emotional well-being and self-efficacy) may have an impact on an individual's ability to work. The aim of this study was to investigate clients' experiences with an individually tailored vocational rehabilitation, the Dirigo project, and encounters with professionals working on it. The Dirigo project was based on collaboration between rehabilitation authorities, individually tailored interventions and a motivational interviewing approach. Methods A descriptive qualitative design was used with data collected through interviews. Fourteen individuals on long-term sick leave took part in individual semi-structured interviews. The interviews were analysed using content analysis. Results The analysis showed overall positive experience of methods and encounters with professionals in a vocational rehabilitation project. The positive experiences were based on four key factors: 1. Opportunities for receiving various dimensions of support. 2. Good overall treatment by the professionals. 3. Satisfaction with the working methods of the project, and 4. Opportunities for personal development. Conclusions The main result showed that the clients had an overall positive experience of a vocational rehabilitation project and encounters with professionals who used motivational interviewing as a communication method. The overall positive experience indicated that their interactions with the different professionals may have affected their self-efficacy in general and in relation to transition to work. The knowledge is essential for the professionals working in the area of vocational rehabilitation. However, vocational rehabilitation interventions also need a societal approach to be able to offer clients opportunities for job training and real jobs.